Research in Economic History. - Christopher Hanes; Susan Wolcott (Emerald, 2014)
Volume 30 contains articles on the economic history of Europe and the U.S. including "Democratization and Central Government Spending, 1870-1938: Emergence of the Leviathan?" by Jari Eloranta, Svetlozar Andreev and Pavel Osinsky; "Swedish Regional GDP 1855-2000," by Kerstin Enflo, Martin Henning and Lennart Schon; "Did the Fed Help to Form a More Perfect Monetary Union?" by John A. James and David F. Weiman; "The Anthropometric History of Native Americans, 1820-1890" by John Komlos and Leonard Carlson; and "The dispersion of customs tariffs in France between 1850 and 1913: discrimination in trade policy," by Becuwe Stéphane and Blancheton Bertrand.
Keywords: Business & Economics -- Economic History.; Economic history.; elektronické knihy; electronic books